The Representation of Men in Online Feminist Magazine Magdalene.Co: A Critical Discourse Analysis - Muhamad Ilham Aditya (Universitas Brawijaya, 2022)
This study attempted to reveal the representation of men in a feminist online magazine named Magdalene.co to perform a transparent relationship between language, social practice, and social structure. For the data analysis, I combined the three-dimensional model from Fairclough (2001) and Halliday’s transitivity (2004). Qualitative approach and document analysis were conducted towards the data in the form of articles taken from Gender and Sexuality rubric. This study found out that there are representations portrayed in Magdalene.co, namely: (1) Men are the Victim of Patriarchy, (2) Men are Socially Pressured and Emotionally Stunted, (3) Men do Have Privileges, (4) Men Need Feminism, and (5) Men Should Freely Express Themselves. These representations occurred mostly in form of active-positive clauses containing relational process. The representations also aligned with the editorial point of view in Magdelene.co which adopts advocacy and gender-sensitive journalism. As the result, Magdalene.co in those articles implied their goals to create a new paradigm regarding masculinity. Furthermore, their goal is influenced by third-wave feminism that leads to the idea of male contribution in feminist movements, such as in Aliansi Laki-laki Baru (ALB). In this case, ALB contributed to the representation in Magdalene.co as the magazine portrayed ALB as the best example of men community in the realm of feminism.